Phenolics metabolism in insects: Pieris brassicae-Brassica oleracea var. costata ecological duo - Ferreres, F. (2011)
Changes in the phenolics composition of Pieris brassicae larvae fasted for distinct periods (1, 2, 4, 6, and 8 h) and their excrements and of Brassica oleracea L. var. costata DC leaves were determined by high-pressure liquid chromatography/UV-photo diode array detector/mass spectrometry- electrospray ionization. This is the first report following phenolics’ metabolism by P. brassicae through time. The results evidence that P. brassicae sequesters and metabolizes the phenolic compounds from the host plant. In a general way, deacylation was the main metabolic reaction that took place, but deglycosylation and sulfate conjugation reactions also occur. Additionally, several kaempferol derivatives containing rhamnose, which is not common in Brassica, were found in the host plant. Attending to the bioactivities recognized for the type of identified compounds, the different materials may constitute an interesting source of bioactive compounds, namely, of highly glycosylated and acylated kaempferol and quercetin derivatives, constituting an economic advantage for producers who have great losses caused by this pest. In addition, a deeper understanding of phenolics metabolism in insects was pursued.